Loss of Dynamin 2 GTPase function results in microcytic anaemia. (3rd May 2017) - Brown, Fiona C.; Collett, Michael; Tremblay, Cedric S.; Rank, Gerhard; De Camilli, Pietro; Booth, Carmen J.; Bitoun, Marc; Robinson, Phillip J.; Kile, Benjamin T.; Jane, Stephen M.; Curtis, David J.
Summary: In a dominant mouse ethylnitrosurea mutagenesis screen for genes regulating erythropoiesis, we identified a pedigree with a novel microcytic hypochromia caused by a V235G missense mutation in Dynamin 2 ( Dnm2 ). Mutations in Dnm2, a GTPase, are highly disease‐specific and have been implicated in four forms of human diseases: centronuclear myopathy, Charcot‐Marie Tooth neuropathy and, more recently, T‐cell leukaemia and Hereditary Spastic Paraplegia, but red cell abnormalities have not been reported to date. The V235G mutation lies within a crucial GTP nucleotide‐binding pocket of Dnm2, and resulted in defective GTPase activity and incompatibility with life in the homozygous state. Dnm2 is an essential mediator of clathrin‐mediated endocytosis, which is required for the uptake of transferrin (Tf) into red cells for incorporation of haem. Accordingly, we observed significantly reduced Tf uptake by Dnm2 +/V235G cells, which led to impaired endosome formation. Despite these deficiencies, surprisingly all iron studies were unchanged, suggesting an unexplained alternative mechanism underlies microcytic anaemia in Dnm2 +/V235G mice. This study provides the first in vivo evidence for the requirements of Dnm2 in normal erythropoiesis.